Implementation of an expert system based on rules to improve the time organization to access the tutoring service (SCIÉNDO INGENIUM, 2023)
The investigative work shows how an expert system based on rules allows to improve the time organization to access the tutoring service at the School of Systems Engineering and Computer Engineering of the Catholic University of Trujillo Benedicto XVI. For this, 8 objects were used with their possible value sets for the development referred to the tutoring service. The knowledge base consisted of 85 inference rules that were formalized thanks to the Tutoring expert. For the implementation, the PHP programming language and the Hypertext Markup Language (HTML) were necessary. With the investigation, it was possible to conclude that through the expert system based on rules, the time organization of tutoring access improved, optimizing appointment assignment and schedule management.
Keywords: Expert system; guidance and counseling service; time organization